All new, all different? : a history of race and the American superhero - Austin, Allan W.; Hamilton, Patrick Lawrence (World comics and graphic nonfiction series., 2019)
Taking a multifaceted approach to attitudes toward race through popular culture and the American superhero, All New, All Different? explores a topic that until now has only received more discrete examination. Considering Marvel, DC, and lesser-known texts and heroes, this illuminating work charts eighty years of evolution in the portrayal of race in comics as well as in film and on television. Beginning with World War II, the authors trace the vexed depictions in early superhero stories, considering both Asian villains and nonwhite sidekicks. While the emergence of Black Panther, Black Lightning, Luke Cage, Storm, and other heroes in the 1960s and 1970s reflected a cultural revolution, the book reveals how nonwhite superheroes nonetheless remained grounded in outdated assumptions. Multiculturalism encouraged further diversity, with 1980s superteams, the minority-run company Milestone's new characters in the 1990s, and the arrival of Ms. Marvel, a Pakistani-American heroine, and a new Latinx Spider-Man in the 2000s. Concluding with a discussion of contemporary efforts to make both a profit and a positive impact on society, All New, All Different? enriches our understanding of the complex issues of racial representation in American popular culture